Judicious and non-judicious use of colistin sulfate in indoor poultry experimentation and its effect on haematological parameters and body weight in broiler - Trisha, Saifa Nasar; Islam, Md Shafiqul; Hasan, Md Rakibul; Hasan Sikder, Md Mahmudul; Akhter Sathi, Most Shumi (Asian-Australasian Journal of Food Safety and Security, 2021)
The aim of this study was to evaluate the effects of discriminate and indiscriminate use of colistin sulfate on body weight and haematological parameters in broiler. Day-old-broiler chicks were collected and reared for up to 31 days. The chicks were randomly divided into control, discriminate and indiscriminate antibiotic group. The discriminate group was treated with colistin sulfate antibiotic (Eskolis-24) for one week (from 16th to 22th day) followed by one week withdrawal period. In case of indiscriminate group, the poultry were treated with colistin sulfate antibiotic for 14 days (from 16th to 29th day) without any withdrawal period until sacrifice. The body weight of the birds were recorded daily. The mean body weight was highest in indiscriminate group (1408.22±133.49 gm) followed by discriminate group (1330.15±134.93 gm) and control group (1243.81±173.19 gm). The differences among means of three groups were not statistically significant. The Total erythrocyte count (Million/mm3) of control, discriminate, and indiscriminate groups were 2.53± 0.05, 2.56±0.08, and 2.52±0.08 respectively. The hemoglobin (gm%) were 7.06± 0.09, 7.03± 0.12, and 7.11±0.09 respectively and the Packed Cell Volume (%) were 19.66±1.11, 19.33±0.95, and 20.16±0.70 respectively. The results found were not statistically significant among the groups for TEC, Hb and PCV respectively. Total lymphocyte (%) count were 67.16±0.60, 70±1.15, and 71.83±1.30 respectively. Total neutrophil (%) count were 32.83± 0.60, 28.83±1.42, and 26.83±1.10 respectively. Total eosinophil (%) count were 0± 0, 1±0.44, and 1.16±0.40 respectively. Total basophil (%) count were zero (0) and total monocyte (%) count were 0± 0, 0.17±0.17, and 0.17±0.17 respectively. In our experiment, both discriminate and indiscriminate groups showed no significant differences of lymphocyte, neutrophil, eosinophil, basophil and monocyte. Therefore, discriminate and indiscriminate use of colistin sulfate for two weeks has no effect on haematological parameters of broiler poultry. Further experiment needed for more concise conclusion. Asian Australas. J. Food Saf. Secur. 2021, 5 (2), 43-54